Zn, Fe, Se, I, phytochemicals assessed in honey and antibacterial activity of sokoto honey on Staphylococcus aureus, and Escherichia coli isolated from WOUND - Nura Maiakwai Salah; AsiyaGidado Yabo; Yusuf Sarkingobir; Aminu Umar Imam; Malami Dikko Imam; Atiku Yari Dogon Daji Imam; Rilwanu Umar Imam; Yusuf Yahaya Miya Imam (International Journal of Advanced Health Science and Technology, 2023)
Antibacterial activity of honey obtained from Specialist Hospital, Sokoto on Staphylococcus aureus and Escherichia coli isolated from wound was studied. the results depicting the levels of iron, selenium, zinc, and iodine micronutrients assessed in honey samples collected from three different zones of Sokoto state, Nigeria. Atomic absorption spectroscopy was used to determine Fe, Zn, se, and I as follows: 7.3± 0.5 to 10.11± 0.15 ppm, 0.50 ± 0.01 to 0.60± 0.01 ppm, 2.6± 0.1 to 11.0 ± 0.05 ppm, 0.05±0.001 to 1.30±0.01 ppm are concentration ranges of Fe, Se, Zn, and I respectively assessed from samples of honey obtained from 3 zones of Sokoto. Agar well diffusion method was used to determine the antibacterial activity of the honey on the test microorganisms. The result revealed that the honey samples have heavy antibacterial activities against the test organisms and zones of inhibition were obtained showing high antibacterial activity. The antibacterial activity increased with increase in the concentrations and the honey produced a high antibacterial activity (clearer zone) on Staphylococcus aureus and Escherichia coli at all concentration. The use of honey as a therapeutic substance has been rediscovered by the medical profession on more recent times, and it is gaining acceptance as an antibacterial agent for the treatment of ulcers and bed sores, and other infections resulting from burns and wounds. Likewise, the honey contains phytochemicals and Zn, Se, Fe, and I micronutrients.